PENINGKATAN KUALITAS HIDUP LANSIA DENGAN PENERAPAN ICOPE - Yuliana, Nuriyah; Yudha C, Anindhita; Damayanti, Damayanti; Tsintani, Tsintani (Jurnal Pengabdian Masyarakat AbdiMas, 2026)
The large number of elderly people and their rapid growth pose various challenges, so the elderly group requires serious attention from all sectors to improve their welfare. One of the steps taken by the government to improve the quality of life of the elderly and health status in Indonesia is by establishing specialized Posyandu for the elderly. Health services at Posyandu for the elderly include physical and mental-emotional health checks that are recorded and monitored using the kartu menuju sehat (KMS) which allows for early detection of diseases or threats that may be faced. WHO proposes the ICOPE approach which involves the integration of health and social care, supported by long-term care systems, to better meet the wishes of older people. ICOPE screening includes: cognitive decline, mobility limitations, malnutrition, vision problems, hearing loss, and depressive symptoms. This program is expected to improve Posyandu services for the elderly, knowledge of health cadres, knowledge of the elderly about ICOPE screening, and improve the health status and quality of life of the elderly. The method applied in this program is to provide counseling and demonstrations on ICOPE screening to cadres and elderly who are active in the elderly Posyandu “Bina Bahagia”. This service activity consists of three phases, namely: preparation, implementation, and closing/evaluation. The expectation of elderly visits to Posyandu is to maintain health status and quality of life in a normal state and as a means of detecting health problems so that they can be immediately overcome or prevented from continuing.